Zjazdy kół krajoznawczych młodzieży w Polsce w pierwszej dekadzie dwudziestolecia międzywojennego - Magiera, Elżbieta (Biuletyn Historii Wychowania, 2019)
Touring and regional trips were among important educational issues in the Second Republic of Poland, conducive to getting to know the immediate environment, regions and the country in general, underpinned by national, patriotic and civic upbringing. In the first decade of the Interwar Period, Poland had three models of school sightseeing clubs developed in Krakow in 1927, in Vilnius in 1928 and in Poznań in 1929. These events provided an opportunity to meet young people from various regions in Poland. Tutors of sightseeing circles; regional, school and church authorities; authorities of sightseeing initiatives launched by adults and the youth, university professors and representatives of urban elites were all participants of the movement. In addition to lectures and speeches, latest issues of the school sightseeing movement were discussed and experiences were shared. As a result, the students and the tutors got to know each other, established contacts and discussed the directions to be followed by school sightseeing clubs. The conventions were accompanied by trips and various forms of presenting the clubs’ achievements including exhibitions, school theatres, singing, dancing, evening performances and others.